Single-Cell RNA Sequencing Unravels Upregulation of Immune Cell Crosstalk in Relapsed Pediatric Ependymoma - Wu, Haoda; Fu, Ruiqing; Zhang, Yu-Hong; Liu, Zhiming; Chen, Zhen-Hua; Xu, Jingkai; Tian, Yongji; Jin, Wenfei; Wong, Samuel Zheng Hao; Wu, Qing-Feng (Frontiers in Immunology, 2022)
Ependymoma (EPN) is a malignant glial tumor occurring throughout central nervous system which commonly presents in children. Although recent studies have characterized EPN samples at both the bulk and single-cell level, intra-tumoral heterogeneity across subclones remains a confounding factor which impedes understanding of EPN biology. In this study, we generated a high-resolution single-cell dataset of pediatric ependymoma with a particular focus on the comparison of subclone differences within tumors, and show upregulation of cilium-associated genes in more highly differentiated subclone populations. As a proxy to traditional pseudotime analysis, we applied a novel trajectory scoring method to reveal cellular compositions associated with poor survival outcomes across primary and relapsed patients. Furthermore, we identified putative cell-cell communication features between relapsed and primary samples and show upregulation of pathways associated with immune cell crosstalk. Our results reveal both inter- and intratumoral heterogeneity in EPN, and provide a framework for studying transcriptomic signatures of individual subclones at single-cell resolution.